The Influence of Character Education and Parenting Patterns on Entrepreneurial Interest with Emotional Intelligence as an Intervening Variable (Study on Vocational Students in Sidoarjo Regency) - Hanik Munaddifah; Nasikh, Nasikh; Wening Patmi Rahayu (Formosa Journal of Applied Sciences, 2023)
Thus, the number of available jobs is not enough to meet the high labor force, causing the unemployment rate to continue to increase. Data from the Central Bureau of Statistics (BPS) shows that the unemployment rate of SMK graduates in 2022 is the highest compared to all levels of education, with a result of 9. The purpose of this study was to determine how the influence of character education and parenting patterns in fostering entrepreneurial interest in vocational students through emotional intelligence. The results of this study indicate that character education and parenting patterns can directly affect entrepreneurial interest. Character education and parenting patterns have a positive and significant influence on emotional intelligence. In addition, character education and parenting patterns have a positive impact and significant effect on entrepreneurial interest in emotional intelligence.